A micropower nanowire interface circuit with sustainable performance - Qu, Yi. (2009)
This report presents a low-cost, low-complexity, high dynamic range conductance to frequency converter with temperature, process and supply voltage variation compensation, which is designed for nanowire sensor interfacing applications. The circuit is based on relaxation oscillator approach. To compensate the temperature and process variation on the ESD current mirror mismatch in the nanowire sensor interface, two sets of ESD current mirrors which performed well under different temperature and process conditions are designed. Together with Vth-extractor circuit and the switch capacitor comparator circuit, the system can sense and select correct ESD current mirrors under different conditions automatically. Meanwhile, with other temperature and process variation compensation techniques on the proposed design such as temperature compensated transconductance of the operational amplifier input transistors in the V-I Converter and switch leakage compensation technique, error brought to the converted frequency of the system is minimized under wide temperature range and various processes. The linearity of the output frequency with respect to nanowire conductance is good. The average accuracy level is 0.357% over a temperature range from 0ºC to 60 ºC in the nanowire sensor range of 100MΩ~1GΩ. And the circuit can operate up to 57ºC for sustained performance under fast case. The worst case conversion error rate of the proposed nanowire sensor interface is 0.908%. The whole circuit is designed in 0.18µm CMOS technology consuming 95.66µW at a single supply of 1.8V and the maximum sensor current.